Вивчення стану ґрунтових вод в умовах міста - Диняк, О.В. (Екологічна безпека та природокористування, 2009)
The technique of systemization and analysis of heterogenious data by form and contents pursuant to the formation of geoinformational database of underground levels has been developed. Uses of means of the spatial analysis and opportunities of integration Geoinformation technologies with the problemoriented modeling systems essentially expand an opportunity of research and an estimation of change of a level of subsoil waters in territories of city agglomerations.